“Smashers” and “Rummies”: Voters and the Rise of Parties in Charlotte County, New Brunswick, 1846‑1857 - Campbell, Gail (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractA case study of a single county helps to explain the rise of political parties in midnineteenth-century New Brunswick. While Charlotte County was not a microcosm of New Brunswick as a whole, fully 10 per cent of the province's population lived there at midcentury. More important, the voting patterns that emerged in Charlotte County did typify the province-wide election results.Three distinct components are necessary to the evolution of a political party: the “organization proper,” composed of party officials and active members; the “party in office,” composed of elected members (caucuses, floor leaders, and whips); and the “party-in-the-electorate,” composed of the individual voters who attached themselves unofficially to the party by regularly supporting it at the polls. The first two components have received a good deal of attention from political historians. The role of the voter, however, has been virtually ignored. This paper seeks to fill that gap in the literature by examining the voting patterns of individual electors during the crucial decade (1846-57) that saw the rise of New Brunswick's first party system. The survival of a run of poll books made possible analysis of patterns of individual participation and response over a series of five elections during the period.The electoral patterns which emerged in Charlotte County during the decade between 1846 and 1857 clearly illustrate the evolution of a party-within-the- electorate. At the beginning of the period, voter response was mainly candidate-oriented. By the end of the period, however, the majority of electors were voting for “slates” of candidates, or parties. The issue which precipitated the transition from a pattern of candidate-based voting to one of party-based voting was temperance. Yet the transition was gradual, extending over a period of three elections, and party-based voting emerged as an outgrowth and extension of candidate-based voting. Throughout the period, voters tended to favour candidates with whom they shared a common identity of interests-people who were, in fact, very like themselves. As politicians formed factions, and then parties, they too formed alliances with others like themselves. Thus, while voters continued to favour candidates with whom they shared a common identity of interests, by 1857 those candidates were running as members of slates representing parties. Voters chose the slate of candidates, or party, whose outlook seemed most in tune with their own. For voters, then, the emergence of party-in-the-electorate represented a conscious shift in orientation, but it required no significant ideological reorientation. For historians, the emergence of party-in-the-electorate, however gradual or imperceptible, is significant, for until parties develop solid support bases among groups of voters, their evolution is incomplete.